2017
DOI: 10.4103/jcd.jcd_97_17
|View full text |Cite
|
Sign up to set email alerts
|

Shear bond strength of different restorative materials to mineral trioxide aggregate and Biodentine

Abstract: Significance of Study:Mineral trioxide aggregate (MTA) and Biodentine (calcium silicate-based materials) have great importance in dentistry. There is no study comparing the bond strength of Biodentine and MTA for composite, compomer, and compomer or resin-modified glass ionomer (RMGIC). Although many advantages of Biodentine over MTA; in this study, MTA has shown better shear bond strength (SBS) to restorative materials.Aim:Recently, a variety of calcium silicate-based materials are often used for pulp capping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
39
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 23 publications
7
39
2
1
Order By: Relevance
“…There are many studies in the literature which studied the bond strength between restorative materials and MTA. Regarding adhesion on Biodentine ® , only eight studies were published [11,18,19,21,24,25,30,31]. Furthermore, the SBS of composite to Biodentine ® using four adhesive systems was investigated for the first time in the present study.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…There are many studies in the literature which studied the bond strength between restorative materials and MTA. Regarding adhesion on Biodentine ® , only eight studies were published [11,18,19,21,24,25,30,31]. Furthermore, the SBS of composite to Biodentine ® using four adhesive systems was investigated for the first time in the present study.…”
Section: Discussionmentioning
confidence: 97%
“…• Group 1 (n = 60): the adhesion process was done after setting time (12 min). To do so, the specimens were randomly divided into four subgroups of 15 specimens [18,24] • Group 2 (n = 60): the adhesion process was done after 24 h in the incubator. To do so, the specimens were randomly divided into four subgroups of 15 specimens.…”
Section: Specimen Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…Although Biodentine offers many advantages over MTA, it presented significantly lower SBS values than MTA to restorative materials, including composite (Filtek Z250, 3M, Saint Paul, MN, USA), compomer (Dyract XP®) and RMGI cement (Photac-Fil Quick Aplicap, 3M, Saint Paul, MN, USA) [116]. On the other hand, another study showed clinically acceptable scores and higher SBS of Biodentine compared to MTA when used with the methacrylate-based composite [53].…”
Section: Biodentinementioning
confidence: 99%